Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s12237-019-00551-z
|View full text |Cite
|
Sign up to set email alerts
|

Hard Structures for Coastal Protection, Towards Greener Designs

Abstract: Over recent years, many coastal engineering projects have employed the use of soft solutions as these are generally less environmentally damaging than hard solutions. However, in some cases, local conditions hinder the use of soft solutions, meaning that hard solutions have to be adopted or, sometimes, a combination of hard and soft measures is seen as optimal. This research reviews the use of hard coastal structures on the foreshore (groynes, breakwaters and jetties) and onshore (seawalls and dikes). The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(126 citation statements)
references
References 84 publications
1
88
0
1
Order By: Relevance
“…In terms of coastal and flood protection, flow or wave attenuation and sediment retention are valuable ecosystem services of coastal and riverine ecosystems (Barbier et al, 2011;Gutiérrez et al, 2011). New insights into the hydraulic efficiency and cost efficiency of natural and nature-based solutions pave the way for integration of such solutions into engineering design processes (de Vriend et al, 2015;Morris et al, 2018;Narayan et al, 2016;Schoonees et al, 2019;Sutton-Grier et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of coastal and flood protection, flow or wave attenuation and sediment retention are valuable ecosystem services of coastal and riverine ecosystems (Barbier et al, 2011;Gutiérrez et al, 2011). New insights into the hydraulic efficiency and cost efficiency of natural and nature-based solutions pave the way for integration of such solutions into engineering design processes (de Vriend et al, 2015;Morris et al, 2018;Narayan et al, 2016;Schoonees et al, 2019;Sutton-Grier et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One way of categorizing nature-based solutions is to distinguish between "fully natural solutions", "managed natural solutions", "hybrid solutions that combine structural engineering with natural features" and "'environment-friendly' structural engineering" ( [31], similar categorization in [32]). To date, guidelines for the design, implementation, monitoring and maintenance of nature-based coastal engineering solutions are limited [31].…”
Section: Existing Framework For Integrating Ecosystems In Coastal Enmentioning
confidence: 99%
“…Based on the findings of the present review, potential for ecological enhancement of sea dikes has been found regarding the foreshore composition, dike surface protection measures (vegetated dike covers, hard revetments and dike roads) and the slope inclination. A schematic sketch of a sea dike system with nature-based solutions is given in [32].…”
Section: Technical and Functional Conception Of Ecologically Valuablementioning
confidence: 99%
“…At present, most of the erosion management strategies involve the use of hard solutions, such as seawalls, interlocking blocks, rubble mound, detached breakwaters, groins, dunes, tyres or jetties [18][19][20][21]. Nevertheless, there are studies indicating that this approach is not the best way to tackle coastal erosion.…”
Section: Introductionmentioning
confidence: 99%